Fatwa tentang Pembiayaan Pengurusan Dana Haji dan Status Dana Calon Haji Daftar Tunggu - Mubarok, Jaih; Hasanuddin, Maulana (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2013)
There are different fatwâ between DSN-MUI and Council Hisbah Persis relating to financing Hajj Arrangements and the status of waiting list hajj candidate. However, in substance, the DSN-MUIFatwâ and is not in contradiction with the Council Hisbah Persis because both fatwas forbid bailout that ta‘alluq between qardh with ujrah. To reach istithâ'ah fi adâ’ al-hajj, a person is prohibited to invade other parties that is istithâ‘ah, MUI fatwa requires that recipients must pay off the fund before the hajj realized. BPIH funds is belong to depositors and is placed at Islamic banks in form of savings or deposit belonging to depositorDOI: 10.15408/aiq.v5i1.2553